"Giant within a giant": a case of typical Kawasaki disease with a giant coronary aneurysm and a large coronary thrombus – a rare case report. (24th August 2017) - Rajasekharan, Sandeep; Kalliath, Suneesh; Govindan, Sajeev C.
Abstract: Kawasaki disease is a febrile vasculitis affecting young children, which may lead to coronary aneurysms. Echocardiography, although sensitive in detecting coronary aneurysms, has a limited role in diagnosing coronary thrombus. Here we report the case of a 10-year-old boy who presented with typical features of Kawasaki disease with giant coronary aneurysms. His follow-up echocardiogram revealed coronary arterial thrombus.